An Analysis of Persuasive Techniques in Airbnb and Booking.com Video Commercials - Reista Fatikah Maldhani; Mariana Ulfah Hoesny (UPT P2M Politeknik Negeri Malang, 2024)
Language is a fundamental tool for human communication and is widely applied across various fields, including advertising, where it serves to inform and persuade audiences about products or services. This study focuses on the use of persuasive techniques—both verbal and non-verbal—in video advertisements, specifically analyzing 20 commercials from Airbnb and Booking.com, two leading online travel agencies with different approaches to targeting audiences. Using a qualitative method and theories from Lamb for verbal and Adler & Rodman for non-verbal techniques, the researcher identified 22 verbal strategies—such as inclusive language, anecdote, and emotive language—with inclusive language being the most dominant, and five non-verbal techniques—like posture, gesture, and facial expression—with posture and gesture being most frequently used.